Communication—Dielectric Dispersion of Chromium Carbide/Copper Calcium Titanate Metacomposites: Epsilon-Negative, Epsilon-Near-Zero, and Inductive Character. (17th February 2021) - Ye, Huan; Li, Yuyan; Qu, Yunpeng; Wang, Zongxiang; Tian, Jiahong; Sun, Kai; Zhao, Yaman; Fan, Runhua
Abstract : Chromium carbide/copper calcium titanate (Cr3 C2 /CCTO) metacomposites were fabricated, wherein epsilon-negative and epsilon-near-zero (ENZ) properties were simultaneously obtained. When Cr3 C2 content exceeds percolation threshold, the formation of Cr3 C2 networks triggers a well-pronounced epsilon-negative behavior. The epsilon-negative property originates from low-frequency plasma oscillation which mainly correlates with concentration of free electrons in Cr3 C2 networks. Epsilon-negative is remarkably achieved at absolutely weak value (∼−10 2 ) at 30 wt% content of Cr3 C2, and negative permittivity was tuned to ∼−10 3 by increasing Cr3 C2 content. Transition of permittivity from positive to negative was accompanied by electrical character changing from capacitive to inductive.